Whose land is it anyway? Contesting urban fringe nature-based tourism and recreation in Western Australia - Hughes, Michael; Tye, Marian; Jones, Roy (Centre for Tourism Research and Development, 2013)
Urban fringe natural areas on public land are important resources for tourism and recreation use. However these contested areas are also in demand for a range of other land uses. How the land is managed can strongly influence opportunities for nature based tourism and recreation, and the benefits that these bring to participants and host communities. This paper examines the case of tourism and recreation access to the forested urban fringe of Perth, Western Australia (WA) using a typology of land occupancy and management priorities originally devised for private land use. A review of legislation and policy relating to tourism and recreation access to land in WA was conducted. Tourism and recreation groups and land managers associated with access to the Perth urban fringe natural areas were interviewed regarding their perceptions of land access management. Most land in the WA study area is publically owned and is therefore technically accessible to the public. In regions dominated by multiple private land owners such as Europe and the UK, varying approaches to land use management may be classified according to a predictable land occupancy typology that tends to be consistently applied. By contrast, the single public land holder in this area of WA, the State Government, lacks consistency in its approach to recreational and tourist access to land. This creates both public and governmental uncertainty and confusion regarding where and how land may be accessed on the Perth urban fringe.